Anticholinesterase activity of β-carboline-1,3,5-triazine hybrids - Paula Baréa; Valéria Aquilino Barbosa; Diego Alberto dos Santos Yamazaki; Carla Maria Beraldi Gomes; Claudio R. Novello; Willian Ferreira da Costa; Gisele de Freitas Gauze; Maria Helena Sarragiotto (Universidade de São Paulo, 2022)
Abstract The β-carboline-1,3,5-triazine hydrochlorides 8-13 were evaluated in vitro against acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE). The analysed compounds were selective to BuChE, with IC50 values in the range from 1.0-18.8 µM being obtained. The N-{2-[(4,6-dihydrazinyl-1,3,5-triazin-2-yl)amino]ethyl}-1-phenyl-β-carboline-3-carboxamide (12) was the most potent compound and kinetic studies indicate that it acts as a competitive inhibitor of BuChE. Molecular docking studies show that 12 strongly interacts with the residues of His438 (residue of the catalytic triad) and Trp82 (residue of catalytic anionic site), confirming that this compound competes with the same binding site of the butyrylthiocholine.